THE IMPACT OF RISK OF POVERTY ON SEGMENTS OF THE MARKET IN ROMANIA - Danu, Cornelia Marcela (Studies and Scientific Researches. Economics Edition, 2014)
In the present work I presented the risk of poverty in Romania considering the economic and social determination. I highlighted that poverty in Romania, is a mix of economic, educational, cultural etc. factors and reinforced by the lack of family or social support. Among the most significant correlative causes of poverty are: lack of money-unemployment, low salaries, lack of money, lack of food-hunger, deprivation, misery, lack of culture, lack of housing, disease, decay, addictions, political causes, individual causes, etc. I analyzed the dynamics of the decision-making behavior of the population of Romania both as a whole and as segments of the market, in terms of age, sex, residence environment, etc. in the market acts, regarding the purchase and consumption decision. The approach and treatment of the poverty must be understand regarding to the systemic economic-social-psychologically interaction. The impact of risk of poverty on the segments of the market is reflected in the production of goods and services; increasing of this type of risk lead to diminishing and modifying the request and further lead to diminishing supply, business failure, etc.